Effect of Temperature Variations on Elevated Temperature Curing Method Towards Modulus of Elasticity and Compressive Strength of Normal Concrete With Additional Accelerator - Yuhanata, Cierio; Nurtanto, Dwi; Utami, Nanin Meyfa (Universitas Jember, 2022)
Developments in modern times have grown rapidly, this can be seen from the rapid development. Along with the increasing scale of development in the world of construction, more and more concrete is needed effectively, practically, and in the future. The strength of concrete is strongly influenced by the quality of the materials, admixtures, the working process, and the curing of the concrete. Concrete with the addition of an accelerator has higher compressive strength, this is due to the accelerator reaction which can accelerate the binding process and the development of the initial compressive strength of the concrete. Concrete with direct immersion treatment has large compressive strength. There are several methods of treating concrete, including watering and high temperature. This study used a fixed accelerator proportion of 3 % of the weight of cement with a test time of 7 and 28 days. The treatment method used is open space, immersion, high temperature at temperatures of 25 ºC, 30 ºC, 35 ºC, 40 ºC and 45 ºC. From the results of the research, there are differences in characteristics between normal concrete and concrete with the addition of an accelerator. Concrete with a high-temperature treatment method at a temperature of 45 ºC produces the highest strong pressure. This is caused by the higher the treatment temperature, the higher the rate of hydration process that affects the compressive strength of the concrete.